UPAYA BIMBINGAN KONSELING DALAM PENGEMBANGAN KARAKTER SISWA - Efa Yuliza (STAI Hubbulwathan Duri, 2017)
Guidance and conseling is an integral part of education that has a position to help students develop a psychosocial aspect consisting of strenghthening the value of virtuous values to produce human resources of character. Characters can not be built only taught to remain internalized through a holistic approach. The government gives 18 values of character education that are described as follows: religious, honest, tolerance discipline hard work, creative, independent, democratic, curiosity, spirit of nasionality love of the homeland, appreciate achievement, friendly/communicative, love to read, care about the environment, social care, and having responsibility. The scope of character education include two aspects of human being that is the inward aspect and the exit aspect. Inward aspect or potential aspects include aspect of cognitive ( if thought), affective (though the heart), and psychomotor (sport) aspects. Exit aspects are in the context of sociocultural aspects in interation with other include interaction in the family, school and community. Each aspect has a space that contains the value of character educational value.